External and Domestic Shocks, Exchange Rate, Country Risk Premia and Macroeconomic Conditions in Turkey - Zekeriya Yıldırım (İstanbul İktisat Dergisi)
The Turkish financial markets have been in turmoil due to the adverse shocks that have originated from both global financial conditions and its domestic political environment. These shocks — especially those caused by the recent political tension in August 2018 — have resulted in a large depreciation in the Turkish lira and a significant increase in Turkey’s country risk premium. This study empirically investigates the macroeconomic consequences of the recent shocks, i.e., the effects of the August depreciation and the recent jump in the risk premium, by estimating a vector autoregression model with monthly data from January 1997 to October 2018. We find that the recent adverse shocks — exchange rate, country risk premium, political risk, and external financial shocks — bring serious macroeconomic consequences, such as a recession and high inflation. To mitigate these adverse effects, policy makers should take immediate measures to restore the investors’ confidence. These measures, in turn, can help to decrease Turkey’s country risk premium and stabilize the Turkish lira.